Espondilodiscitis multifocal y meningoencefalitis por Staphylococcus aureus en un paciente inmunocomprometido - Joana Marques Dias; Carolina Cabrita Abreu; Ana Grilo; Fernando Martos Gonçalves (Sociedade Galega de Medicina Interna, 2024)
Spondylodiscitis is a rare diagnosis, but its incidence has increased in recent years. It represents 3-5% of osteomyelitis, and the multifocal affliction is rare as it occurs in 4-8% of all spondylodiscitis. The occurrence of meningoencephalitis associated with spondylodiscitis is also a rare association. We present the case of a 54-year-old woman diagnosed with multifocal spondylodiscitis complicated with meningoencephalitis and intracanal and paravertebral abscess with identification in blood cultures of Staphylococcus aureus. Immunosuppression with infliximab was identified as a risk factor. The patient underwent targeted antibiotic therapy, opting for the conservative strategy due to the surgical risk. There was a positive evolution with imaging resolution of the intracanal abscess. This case is of particular importance due to its rarity of frequency and considering the etiological agent and the low frequency of this infection in patients under anti-TNF-alpha therapy.